A new ophiocistioid with soft-tissue preservation from the Silurian Herefordshire Lagerstätte, and the evolution of the holothurian body plan - Rahman, IA; Thompson, JR; Briggs, DEG; Siveter, DJ; Siveter, DJ; Sutton, MD (Royal Society, 2019)
Reconstructing the evolutionary assembly of animal body plans is challenging when there are large morphological gaps between extant sister taxa, as in the case of echinozoans (echinoids and holothurians). However, the inclusion of extinct taxa can help bridge these gaps. Here we describe a new species of echinozoan, Sollasina cthulhu, from the Silurian Herefordshire Lagerstätte, UK. Sollasina cthulhu belongs to the ophiocistioids, an extinct group that shares characters with both echinoids and holothurians. Using physical–optical tomography and computer reconstruction, we visualize the internal anatomy of S. cthulhu in three dimensions, revealing inner soft tissues that we interpret as the ring canal, a key part of the water vascular system that was previously unknown in fossil echinozoans. Phylogenetic analyses strongly suggest that Sollasina and other ophiocistioids represent a paraphyletic group of stem holothurians, as previously hypothesized. This allows us to reconstruct the stepwise reduction of the skeleton during the assembly of the holothurian body plan, which may have been controlled by changes in the expression of biomineralization genes.